A Development Model of Learning Management in the Subject of Modern Literary Criticism Using the Principles of Buddhist Teaching Methods for Undergraduate Students in Thai Language Teaching Program at Mahachulalongkornrajavidyalaya University - (Thongsa Ṭhānissaro), Phrasripariyattithada; Phrakrukhamphithammanuwat; Sribunrueang, Pacharakit (Journal of Buddhist Education and Research (JBER), 2026)
This research and development study aimed to: 1) investigate the current state of learning management in Modern Literary Criticism using Buddhist instructional principles; 2) develop a learning management model based on Buddhist teaching methods; 3) implement the developed model; and 4) evaluate its effectiveness. The study was conducted in four phases, namely situation analysis, model development, implementation, and evaluation. The target groups consisted of administrators, instructors, undergraduate students majoring in Thai Language Teaching at Mahachulalongkornrajavidyalaya University, experts, and administrators of Khon Kaen Buddhist College, totaling 119 participants. The research instruments included questionnaires, focus group discussion records, model evaluation forms, a model handbook, an achievement test, and a satisfaction questionnaire. Data were analyzed using mean and standard deviation. The findings revealed that the overall state of learning management in Modern Literary Criticism based on Buddhist instructional principles was at a high level (x̄ = 3.82). The developed model comprised five components: principles, objectives, content, learning management process, and assessment and evaluation, with overall appropriateness, feasibility, and usefulness rated at a high level (x̄ = 4.10). The model achieved an efficiency score of 81.67/84.31, exceeding the established criterion of 80/80. Students’ post-test achievement scores were significantly higher than their pre-test scores at the .05 level, and their satisfaction with the model was at a high level (x̄ = 4.42). Furthermore, the overall evaluation of the model implementation was at the highest level (x̄ = 4.68). The results indicate that the developed learning management model based on Buddhist teaching methods effectively enhances students’ learning achievement and promotes learning in Modern Literary Criticism, making it suitable for application in higher education contexts.